2011
DOI: 10.1165/rcmb.2009-0140oc
|View full text |Cite
|
Sign up to set email alerts
|

Notch Induces Myofibroblast Differentiation of Alveolar Epithelial Cells via Transforming Growth Factor–β–Smad3 Pathway

Abstract: Notch is an ancient cell-signaling system that regulates the specification of cell fate. This study examined the role of Notch in the epithelial-mesenchymal transition (EMT) and myofibroblast differentiation of cultured RLE-6TN cells (i.e., rat alveolar epithelial cells). The activation of Notch, either by ectopic expression of the Notch intracellular domain or by the co-culture of RLE-6TN cells with L-Jagged1 cells, induces the expression of smooth muscle α-actin (SMA) and other mesenchymal marker genes (coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 44 publications
3
43
0
1
Order By: Relevance
“…However, in 10T1/2 fibroblasts, Notch3 represses expression of smooth muscle target genes including α- SMA by inhibition of the activation of Smad3 and p38 mitogen-activated protein kinase [58]. In contrast, in alveolar epithelial cells, Notch1 induces the phosphorylation of Smad3 and activates α- SMA gene transcription in a SRF-binding site [CC(A/T) 6 GG, termed CArG box]-dependent and TGFβ control element-dependent manner [59]. Other experiments also suggest that Notch1 suppresses fibroblast proliferation that depends on Wnt11-dependent WISP-1 expression [60].…”
Section: Regulation Of Myofibroblast Differentiationmentioning
confidence: 99%
“…However, in 10T1/2 fibroblasts, Notch3 represses expression of smooth muscle target genes including α- SMA by inhibition of the activation of Smad3 and p38 mitogen-activated protein kinase [58]. In contrast, in alveolar epithelial cells, Notch1 induces the phosphorylation of Smad3 and activates α- SMA gene transcription in a SRF-binding site [CC(A/T) 6 GG, termed CArG box]-dependent and TGFβ control element-dependent manner [59]. Other experiments also suggest that Notch1 suppresses fibroblast proliferation that depends on Wnt11-dependent WISP-1 expression [60].…”
Section: Regulation Of Myofibroblast Differentiationmentioning
confidence: 99%
“…In contrast, lung epithelial cell-specific deletion of β-catenin results in blocked alveolar epithelial cell differentiation, resulting in a lung structure composed primarily of conducting airways, thus demonstrating a critical requirement of β-catenin for regular formation of alveoli (129). In IPF, the Wnt/β-catenin developmental network is one of the core signal signaling (93,(136)(137). Interestingly up to now, there is neither data on the Notch signaling pathway element expression in IPF nor on the influence of Notch activation on alveolar epithelial proliferation, differentiation or survival.…”
Section: H 24h and 48h 48hmentioning
confidence: 99%
“…The rationale for examining the Notch pathway in lung fibrosis does not exclusively stem from the knowledge of the influence of Notch on the regenerative response to injury in adult tissue (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141) but also from a growing number of studies showing that Notch signaling may play a significant role in the process of fibrosis in organs such as kidney, skin and heart (95,98,142). In addition, reactivation of Moreover, results reflecting our data were described by Ma et al who revealed that NICD3 and Hey1 are upregulated after 5-fluorouracil induced injury of the rat tracheal epithelium (144).…”
Section: Reactivation Of the Notch Signaling Pathway In Lung Fibrosismentioning
confidence: 99%
“…The pathologic activation of Notch signaling has been implicated in the pathogenesis of various malignancies and fibrotic diseases, such as systemic sclerosis and idiopathic pulmonary fibrosis6,7,8. The inhibition of Notch signaling has been adopted in clinical trials to treat several malignant tumors such as gastrointestinal neuroendocrine tumors, metastatic thyroid cancer, and advanced breast cancer2.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of the TGF-β signaling pathway is considered to be the main pathogenesis of fibrotic skin diseases such as keloids11. There is evidence that the Notch signaling pathway exerts its effects via upstream or downstream signaling transduction of the TGF-β signaling pathway6,12. A recent study showed that NICD and hes-1 levels increased in skin fibroblasts stimulated by TGF-β in patients with systemic sclerosis9,10.…”
Section: Introductionmentioning
confidence: 99%